72=9p

Rewrite the equation as 9p=72.

9p=72

To remove the radical on the left side of the equation, square both sides of the equation.

(9p)2=722

Apply the product rule to 9p12.

92(p12)2=722

Raise 9 to the power of 2.

81(p12)2=722

Multiply the exponents in (p12)2.

Apply the power rule and multiply exponents, (am)n=amn.

81p12⋅2=722

Cancel the common factor of 2.

Cancel the common factor.

81p12⋅2=722

Rewrite the expression.

81p1=722

81p1=722

81p1=722

Simplify.

81p=722

Raise 72 to the power of 2.

81p=5184

81p=5184

Divide each term in 81p=5184 by 81.

81p81=518481

Cancel the common factor of 81.

Cancel the common factor.

81p81=518481

Divide p by 1.

p=518481

p=518481

Divide 5184 by 81.

p=64

p=64

Solve for p 72=9 square root of p